2012
DOI: 10.1111/j.1469-8749.2011.04215.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnetic resonance imaging in the follow‐up of children with convulsive status epilepticus

Abstract: CSEConvulsive status epilepticus GOSH Great Ormond Street Hospital HIMAL Hippocampal malrotation PFS Prolonged febrile seizure STEPIN Status Epilepticus Imaging and Neurocognitive Study AIM The aim of this study was to determine the yield of magnetic resonance imaging (MRI) after an episode of childhood convulsive status epilepticus (CSE) and to identify the clinical predictors of an abnormal brain scan.METHOD Children were recruited following an episode of CSE from an established clinical network in north Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…We prospectively recruited children aged 1–42 months who had at least one episode of CSE between December 2006 and March 2010. Patients were recruited from north London hospitals using a recruitment strategy similar to the North London Convulsive Status Epilepticus Surveillance study (Chin et al., ), which is described in detail elsewhere (Yoong et al., ). In brief, we collected baseline clinical data and arranged for the child to have a magnetic resonance imaging (MRI) scan and neuropsychological assessments at University College London Institute of Child Health (ICH)/Great Ormond Street Hospital (GOSH) at the parents' earliest convenience.…”
Section: Methodsmentioning
confidence: 99%
“…We prospectively recruited children aged 1–42 months who had at least one episode of CSE between December 2006 and March 2010. Patients were recruited from north London hospitals using a recruitment strategy similar to the North London Convulsive Status Epilepticus Surveillance study (Chin et al., ), which is described in detail elsewhere (Yoong et al., ). In brief, we collected baseline clinical data and arranged for the child to have a magnetic resonance imaging (MRI) scan and neuropsychological assessments at University College London Institute of Child Health (ICH)/Great Ormond Street Hospital (GOSH) at the parents' earliest convenience.…”
Section: Methodsmentioning
confidence: 99%
“…The edema manifested as increases in hippocampal volume and increases in T2 relaxation time. A second cohort of 33 children ascertained in London did not have acute MRI, but had imaging at 3 months, 6 months and 1 year following the acute event in order to define the course of hippocampal injury after the initial hippocampal edema had resolved [16]. FEBSTAT has recruited 199 children with FSE and therefore has greater power to detect abnormalities than the London study.…”
Section: Hippocampal Injurymentioning
confidence: 99%
“…The London study identified one child (3%) with a minor abnormality [hippocampal malrotation (HIMAL)] and no children with a major abnormality [16]. The London study identified one child (3%) with a minor abnormality [hippocampal malrotation (HIMAL)] and no children with a major abnormality [16].…”
Section: Nonhippocampal Imaging Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We fashioned our HT group to evaluate febrile convulsions. Febrile convulsions are common among children, and 31% of the MR imaging (MRI) studies of children with febrile status epilepticus have shown anomalies (Yoong et al., 2012). Other studies also asserted that the presence of an underlying focal CD leads to a prolongation of febrile seizures (Bocti et al., 2003; Scantlebury & Heida, 2010) as well as higher mortality rates (Pujar et al., 2011).…”
Section: Cortical Dysplasia Epilepsy and Treatment Strategiesmentioning
confidence: 99%